KORELASI ANTARA GAYA BELAJAR DAN MOTIVASI BELAJAR SISWA KELAS IV SD GUGUS UBUD KECAMATAN UBUD TAHUN PELAJARAN 2017/2018 - Anak Agung Inten Mahayanti (Universitas Pendidikan Ganesha, 2018)
The research was aimed at determining the significant correlation between learning style and learning motivation of the fourth-grade students in Gugus Ubud Elementary School Ubud Sub-district in the academic year 2017/2018. The study used ex-post facto research by using Product Moment correlation technique and multiple-linear regression. The population of this research was all students in the fourth-grade of Gugus Ubud in the academic year 2017/2018 consisting of 205 students. The samples were obtained using proportional random sampling so that 150 students were chosen in this research.The data were collected using non-test method which used the questionnaire of learning style and learning motivation as the instrument. The result of the research was analyzed using descriptive statistic analysis and inferential statistic analysis research by using product moment correlation technique and multiple-linear regression in which the prerequisite tests were normality test, linearity test, and multicollinearity test. The analysis shows that: (1) there is the significant correlation between visual learning style and learning motivation in which rx1y = 0,277 and ry1.23 =0,214 >rtable5% = 0,159 as well as effective contribution = 4,9%, (2) there is the significant correlation between the auditory learning style and learning motivation in which rx2y = 0,556 and ry2.13 = 0,509 as well as the effective contribution = 27,4%, (3) there is the significant correlation between the kinesthetic learning style and learning motivation in which rx3y = 0,253 and ry3.12 = 0,168 as well as the effective contribution = 3,5%, (4) simultaneously, there is the significant correlation between the visual, auditory, and kinesthetic learning style and the learning motivation of the four-grade students of in Gugus Ubud Elementary School Ubud Sub-district in the academic year 2017/2018 in which Fcount = 27,186 > Ftable = 2,68 as well as the effective contribution = 35,8%.